Dividends, Leverage and Endogeneity: A Simultaneous Equations Study on Malaysia - Maziar Ghasemi; Nazrul AB Razak; Junaina Muhamad (Australasian Accounting, Business and Finance Journal, 2018)
Drawing upon preceding empirical studies on the potential endogeneity of both debt and dividends in developed markets, this study investigates two-way causal relationships that can exist between payout decisions and debt policies in Malaysian listed companies. The analysis is performed by applying a simultaneous equations model (SEM) on a sample of 267 listed firms on the Main board of Bursa Malaysia during 2006–2014. The main findings indicate that when dividend is treated as endogenous, there is a positive impact on leverage. However, leverage is found to have a simultaneous negative impact on dividends. The findings also show that liquidity and performance positively affect dividends, although they have a negative effect on leverage. Additionally, this study documents an inverse relation between tangibility and debt, a direct relation between reputation and debt, and also confirms that larger firms tend to pay out a higher percentage of dividends per share.
Keywords: Agency Theory; Bursa Malaysia; Dividends; Endogeneity; Leverage; Simultaneous Equations Models.